(3GNJjGQ ef OhGhjf GdeJfHj hGdHMJQj hGHj JeGes - (3GdLQLGfj , YHO GdbGgQ Hf YHO GdQMef Hf eMeO, CHh HcQ,J (B471 (3g` s ((3CHhGdYdG Hf CHj GdahGQS s)
(3ChdgG (B:s
(3hHOCfG HTYQ GdoeJfHj bGd CHhGdWjH GdoeJfHj(B: (3EfeG GdJgfjGJ ddCcaGA hdef jOfj ef GdHYOGA s
(3BNQgG (B:s
(3hgd ef LGA HYO GdaJM jSYi dUGMH gLQJjf eY GdfHj Je eG GNJGQg ef OjhGf CHj JeGe s
(3Vef eLehY , JQJjHgG (B: (3ef U (B116 (3H (B- (3U(B148s
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3JHUQI GdYfhGf (B:s
(3GNJjGQ s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B48 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B5 - (3U (B310s
Keywords: (3GdCOHs